Pengaruh Konsentrasi Sari Jahe Merah (Zingiber Officinale Var. Rubrum) Dan Lama Penyimpanan Terhadap Jumlah Mikrobia Pada Susu Kedelai - QOMSAH, SAFROTUL; , Eni Purwani, S.Si, M.Si; , Endang Nur W, SST., M.Si Med (2016)
Introduction: Soybean milk is a product derived from fluid of soybean grinding by using hot water. Soybean milk, which is contained of much nutrients, could become growing media and good dissemination for pathogen bacteria so that nutrient content is damaged or flavor become stale. Red gingers have higher gingerol and taste spicier than other gingers. Gingerol acts as anti-microbe compopunds, so it could effect the amount of microbe. Objective: The purpose of the research was to determine the effect of concentration red ginger extract and storage time towards the amount of microbes on soybean milk. Method: The types of research used an experimental design with a completely randomized design and factorial arrangement. Concentration red ginger was 0%, 1,5%, 2,5%, and 3,5%. Variation of storage time was 0 hour, 3 hours, 6 hours, and 9 hours. The amount of microbe was tested by TPC method. The amount of microbe was analyzed by using Kruskal-Wallis dan GLM-Univariate. The difference of the results were analyzed by using Duncan 5%. Result: The results of the research showed that the lowest amount of mircobe in soybean milk was at concentration red ginger of 1,5% (2,1x107 cfu/ml), while based on storage time, the highest amount of microbe was at storage time of 9 hours (5,8x107 cfu/ml). Conclusion: There was the effect of concentration red ginger extract (p=0,024) and storage time (p=0,032) on soybean milk.